Current scenario of emerging pollutants in farmlands and water reservoirs: Prospects and challenges - Muhammad Fahad Sardar; Fazila Younas; Hongna Li; Jawad Ali; Pengcheng Zhu; Xiaona Yu; Zhaojie Cui; Weihua Guo (Ecotoxicology and Environmental Safety)
Globally, roughly more than 400 million metric tons of plastics are produced annually. Similarly, the pharmaceuticals business is rising exponentially yearly, 5.8 %. It is expected to increase from USD 714 billion to USD 1454 billion by 2029. Beyond their intended uses, these substances are released into the environment as contaminants due to improper usage and management practices. Therefore, pharmaceuticals and microplastics (MPs) are classified as emerging pollutants (EPs), and their existence in agricultural ecosystems adversely affects soil and environmental health, ultimately impacting both ecological and human well-being. Pharmaceuticals and MP-loaded organic amendments (especially manure) are a primary cause of emerging soil pollutants. The increasing application of treated wastewater or biosolids as irrigation water or soil conditioners, mainly when derived from untreated sewage sludge, can introduce pharmaceuticals and MPs into the farmlands, merging these pollutants within the soil medium. The co-occurrence of MPs and pharmaceuticals leads to prolonged environmental presence and gradual bioaccumulation in organisms over time, contributing to persistent contamination and long-lasting effects on ecosystems. Moreover, these EPs have the potential to alter the composition of soil biogeochemistry and disrupt overall soil health and productivity. Numerous methods have been developed to address this emerging issue, including electrochemical degradation, advanced oxidation processes, photocatalytic degradation, biosurfactants, micro- and nano-bubble systems, ultrasonic cavitation, nanotechnology, constructed wetlands, and many hybrid approaches. This review explores the extent of EPs, their interactions, and management strategies in EPs-contaminated environments.